Combined Hepatotoxicity and Toxicity Mechanism of Intermedine and Lycopsamine - Ziqi Wang; Liang Qiao; Qinqin Zheng; Haolei Han; Zuguang Li; Xiangchun Zhang; Hongping Chen (Toxins, 2022)
Pyrrolizidine alkaloids (PAs) are common constituents of plants and have serious hepatotoxicity. Intermedine (Im) and lycopsamine (La) are two monoesters of PAs that frequently coexist in the PA-containing plants (e.g., comfrey and tea). The present study aimed to explore the combined hepatotoxicity and toxicity mechanism of the Im and La mixture. In vitro, the combined cytotoxicity of the Im and La mixture on human hepatocytes (HepD) was examined by CCK-8, colony formation, wound healing, and Annexin V/PI staining assays. The combination of Im and La inhibited the ability of HepD cells to proliferate, colonize, and migrate and induced hepatocytes apoptosis in a dose-dependent manner. In addition to significantly causing a burst of intracellular reactive oxygen species (ROS), mitochondrial apoptosis, and endoplasmic reticulum (ER) stress, the Im and La mixture can also cause an increase in intracellular Ca2+, triggering the PERK/eIF2α/ATF4/CHOP apoptosis pathway. This study provided the first direct evidence that the combined PAs induced hepatotoxicity through ER-mediated apoptosis. These results supplemented the basic toxicity data for the combined PAs and provided a new perspective for the risk assessment of combined PA toxicity.